Feed Diversity, Palatabiliti and Carrying Capacity of Sumatran Elephant (Elephas maximus sumatranus) Flying Squad in Tesso Nilo National Park. - Rizki Kurnia Tohir (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Flying Squad (FS) WWF is a human-elephant conflict mitigation program that has been operated for 13 years. This program operates in Tesso Nilo National Park (TNNP) at high conflict density. The management of FS captive elephant is performed by grazing in TNNP forest area. The existence of grazing activities, the operational time and the threat of deforestation will certainly affect the availability of feed and feed carrying capacity. This study aims to analyze feed diversity, palatability, and feed carrying capacity at the operational area. The method used for this study are 60 plots of vegetation analysis, interview, literature study and destructive measurement method by making 30 productivity plots of ground cover plants and observed for 2 months. The study found 110 feed species from 47 families. Within 6 hours of palatability observation, average elephant can grab the feed for 1959 time and the highest feed palatability is Rhynchospora corymbosa (L.) Britton. The total of feed productivity from ground cover plants is 82.027 kg/day. Carrying capacity at 1714 ha area is 161 elephants.